Resistance Against Beauty Standards Stereotypes and Representation of Women’s Beauty Through BLP Beauty Advertisement - Tanca, Jhenika Tiara (Universitas Medan Area, 2024)
Advertising is a medium for conveying persuasive messages to promote a product or brand. Many advertisers strive to find interesting concepts to capture the audience's attention. The use of beautiful women in advertisements, especially in cosmetic ads, is a common occurrence. Eventually, these ads construct a media representation that reinforces stereotypes of women's beauty standards. One of the cosmetic advertisements that will be the subject of this research is the BLP Beauty #BLPMainCharacter ad on the official Instagram account @blpbeauty, uploaded from May 8, 2023, to May 12, 2023. This research aims to understand how BLP Beauty offers their cosmetic products for women who want to enhance their beauty without conforming to existing beauty stereotypes. The research method used is qualitative descriptive with semiotic analysis by Roland Barthes. Semiotics is the study of signs within a text. The signs in the text are considered to have denotative meaning (dictionary meaning) and connotative meaning (dual meaning born from cultural and personal experiences). This research positions BLP Beauty advertisements as a text that will be analyzed to uncover the true meanings behind the signs contained within the ads. The results of this research analysis explain that BLP Beauty resists the standard beauty stereotypes by introducing a new concept in representing women's beauty. The resistance in this research is a form of opposition or rejection of stereotypes or inequalities related to women's beauty standards. BLP Beauty emphasizes that beauty in women goes beyond physical attributes like fair skin, slim bodies, straight hair, and various other beauty stereotypes but is unique to each woman. This is demonstrated through the selection of models who defy the conventional description of beauty in society. BLP Beauty boldly chooses models with larger bodies, darker skin, chubby faces, and various criteria that oppose the stereotype of beautiful women in society. BLP Beauty emphasizes that all women are beautiful in their uniqueness. It is hoped that this resistance movement can be the beginning of a revolution for women in the advertising world and will broaden society's perspective on the definition of women's beauty.